Analisis Keuntungan Usaha Keripik Pisang Goroho Manalagi Di Kelurahan Dendengan Dalam Kecamatan Paal Dua Kota Manado - Pelealu, Revina Gita; Kaunang, Rine; Wariki, Barce Andries Feriano (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the profits of the Goroho Manalagi Banana Chips business in Dendengan Dalam Village, Paal Dua District, Manado City. This research was carried out from June 2023 to August 2023. The data used in this study are primary data and secondary data. Primary data was obtained from interviews and observations as well as documentation with business owners, while secondary data was obtained from literature studies in the form of literature, written sources or documents that have relevance to this research. The data analysis used is Total Revenue, Total Cost and Profit. The results of the study show that, the analysis of the profits of the Goroho Manalagi banana chips business for 5 days of production can be concluded that the cost of banana chip production is IDR 3.459.683,04 and the revenue is IDR 4,277,000.00 so that the profit obtained in one week is IDR 817.316,96.